2022
DOI: 10.1039/d2cc00792d
|View full text |Cite
|
Sign up to set email alerts
|

Dual-amplified CRISPR-Cas12a bioassay for HIV-related nucleic acids

Abstract: Nucleic acid amplification strategies successfully dominated ultrasensitive bioassay, whereas sometimes brought high time-consumption, multi-step operation, increased contamination risk, and mismatch-related inaccuracy. We proposed a nucleic acid amplification-free method called AuNPs-tagging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…After magnetic separation, the number of remaining PtNP tags in the supernatant was directly counted by sp-ICP-MS, exhibiting a considerable correlation against CEA. In accordance with references from other leading research groups and our previous studies, 11,49,50 the proposed method could also be utilized in nucleic acid binding or assay research and other types of interface reactions. We also carried out a size (diameter) optimization of nanoparticles on the binding efficiency and discussed the results, screening the suitable size of PtNPs (34 nm) with high efficiency for differential immunoassay.…”
Section: ■ Conclusionsupporting
confidence: 79%
“…After magnetic separation, the number of remaining PtNP tags in the supernatant was directly counted by sp-ICP-MS, exhibiting a considerable correlation against CEA. In accordance with references from other leading research groups and our previous studies, 11,49,50 the proposed method could also be utilized in nucleic acid binding or assay research and other types of interface reactions. We also carried out a size (diameter) optimization of nanoparticles on the binding efficiency and discussed the results, screening the suitable size of PtNPs (34 nm) with high efficiency for differential immunoassay.…”
Section: ■ Conclusionsupporting
confidence: 79%
“…Lv et al developed a CRISPR-Cas12a-based assay for the detection of HIV-related DNA using the ICP-MS signal of AuNPs (Figure 9A). [108] In this work, the 3'-end of the probe bound to AuNPs and the 5'-end was connected with magnetic beads. When the target was present, the trans-cleavage activity of the CRISPR-Cas12a system was activated to cleave AuNPstagged probes, leading to the release of AuNPs from the surface of magnetic beads.…”
Section: Other Biosensorsmentioning
confidence: 99%
“…Reproduced with permission. [ 108 ] Copyright 2022, Royal Society of Chemistry Publishing Group. B) A biosensor based on the AuNPs heterodimers for the detection of GCSCs.…”
Section: Cas12a‐based Biosensors Using Gold Nanomaterialsmentioning
confidence: 99%
“…Since the discovery of Cas12a, the trans-cleavage reaction substrate, which is labeled with a fluorophore and quencher, has been designed to be 5–7 nucleotides (nt) in length to achieve better response efficiency. However, the length of the substrate has not been thoroughly explored. Only a few studies have focused on optimizing the reaction conditions of the Cas12a detection system. Ma et al found that divalent metal ions in the buffer affected Cas12a’s activity and that manganese ions can enhance the signal up to 13-fold compared to magnesium ions . Rossetti et al used a hairpin reporter instead of a linear reporter, which reduced the detection limit by about 15 times .…”
mentioning
confidence: 99%
“…Rossetti et al used a hairpin reporter instead of a linear reporter, which reduced the detection limit by about 15 times . Some researchers have attempted to label the reporter on gold nanoparticles, which can also reduce the detection limit by about 20 times. , Additionally, some complex designs, such as modifying the relevant sequences or using a non-fluorescent reporter system, have also been proposed to improve detection results. However, the improvements achieved by these optimization methods are not significant, and some methods are complicated. Moreover, there is a lack of thorough investigation into the optimization of reaction conditions for the CRISPR-Cas12a system, such as the Cas12a/crRNA ratio, buffer composition, and substrate structure.…”
mentioning
confidence: 99%